2012
DOI: 10.1212/wnl.0b013e31824528a0
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem verification of MS cortical lesion detection with 3D DIR

Abstract: Objective: To assess the sensitivity and specificity of 3D double inversion recovery (DIR) MRI for detecting multiple sclerosis (MS) cortical lesions (CLs) using a direct postmortem MRI to histopathology comparison.Methods: Single-slab 3D DIR and 3D fluid-attenuated inversion recovery (FLAIR) images of 56 matched fresh brain samples from 14 patients with chronic MS were acquired at 1.5 T. The images of both sequences were prospectively scored for CLs in consensus by 3 experienced raters who were blinded to his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
197
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 214 publications
(210 citation statements)
references
References 32 publications
8
197
0
5
Order By: Relevance
“…Previous studies at 1.5T detected only 31% 3 or 56% 16 of intracortical lesions with a T2WI sequence and 29% with a DIR sequence. 17 With a FLAIR sequence, 9%, 17 21%, 3 or 71% 18 of intracortical lesions were detected retrospectively. Compared with previous postmortem MR imaging studies at ultra-high-field (7T) strength, our T2WI and T2*WI retrospective detection rates are higher than the 67% found with R2* maps, 19 comparable with the 82% found with WM-attenuated turbo field echo, and slightly lower than the 93% detected with T2*WI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies at 1.5T detected only 31% 3 or 56% 16 of intracortical lesions with a T2WI sequence and 29% with a DIR sequence. 17 With a FLAIR sequence, 9%, 17 21%, 3 or 71% 18 of intracortical lesions were detected retrospectively. Compared with previous postmortem MR imaging studies at ultra-high-field (7T) strength, our T2WI and T2*WI retrospective detection rates are higher than the 67% found with R2* maps, 19 comparable with the 82% found with WM-attenuated turbo field echo, and slightly lower than the 93% detected with T2*WI.…”
Section: Discussionmentioning
confidence: 99%
“…For 3D-FLAIR, there are many reports regarding application to multiple sclerosis. 5,6,[42][43][44][45][46][47][48][49][50][51][52][53][54] Smaller lesions can be detected by 3D-FLAIR than by 2D-FLAIR due to thinner slices and fewer flow artifacts with 3D-FLAIR. 45,46 Excellent detection of cortical lesions by 3D-FLAIR has also been reported (Fig.…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…4,5 The double inversion recovery sequence improves detection but does not reveal most CL. 5,6 While nonquantitative imaging features low sensitivity to CL, the sensitivity of semiquantitative and quantitative MRI is unclear. Although one ex vivo imaging study performed at 1.5 T revealed that T1 and T2 relaxation rates (not magnetization transfer ratio [MTR]) are sensitive to CL, 7 a separate study performed at 9.4 T found MTR and T2 relaxation rate (not T1) to be most sensitive.…”
Section: Introductionmentioning
confidence: 99%